ASSOCIATION BETWEEN LONG-TERM ASPIRIN USE AND FRAILTY IN MEN: THE PHYSICIANS' HEALTH STUDY. (20th December 2022) - Orkaby, Ariela; Yang, Laiji; Dufour, Alyssa; Travison, Thomas; Sesso, Howard; Driver, Jane; Djousse, Luc; Gaziano, J
Abstract: The role of anti-inflammatory medications such as aspirin to prevent frailty is unknown. We studied 12, 101 men ≥60 years who participated in the Physicians' Health Study I, a completed aspirin trial. Annual questionnaires collected data on aspirin use, lifestyle, and clinical variables. Average aspirin use was dichotomized: ≤60 vs >60 days/year. Frailty was assessed using a 33-item index. Propensity score methods addressed confounding by indication. Logistic regression models estimated odds of frailty as a function of categories of average aspirin use. Mean age was 71 years. Following an average of 11 years of follow-up, 15% reported aspirin use ≤60 days/year; 20% were frail. The OR (95%CI) for frailty was 0.85 (0.76-0.96) for average aspirin use >60 days/year vs ≤60 days/year. Results were similar using an alternate definition of frailty. Long-term regular aspirin use is inversely associated with frailty among older men, even after consideration of multi-morbidity and health behaviors.